2011
DOI: 10.1002/elps.201000475
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fluoroacetate and fluoride in blood serum by capillary zone electrophoresis using capacitively coupled contactless conductivity detection

Abstract: Fluoroacetate is a highly toxic species naturally found in plants and in commercial products (compound 1080) for population control of several undesirable animal species. However, it is non-selective and toxic to many other animals including humans, and thus its detection is very important for forensic purposes. This paper presents a sensitive and fast method for the determination of fluoroacetate in blood serum using capillary electrophoresis with capacitively coupled contactless conductivity detection. Serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…In clinical analysis, the research was focused mainly on non‐UV‐absorbing species and the determination of small inorganic ions was shown in various body fluids . Other small ions, such as fluoride and fluoroacetate and a range of organic acids , were also analyzed by CE‐C 4 D. It was also shown that CE‐C 4 D can be applied in the determination of increasing concentrations of plasma lactate during exercise testing . Phenylated organic acids were monitored in urine samples as a potential diagnostic tool for determination of phenylketonuria using MEKC with dual C 4 D/amperometric detection .…”
Section: Applications Of Electrophoresis Methods With Conventional Camentioning
confidence: 99%
“…In clinical analysis, the research was focused mainly on non‐UV‐absorbing species and the determination of small inorganic ions was shown in various body fluids . Other small ions, such as fluoride and fluoroacetate and a range of organic acids , were also analyzed by CE‐C 4 D. It was also shown that CE‐C 4 D can be applied in the determination of increasing concentrations of plasma lactate during exercise testing . Phenylated organic acids were monitored in urine samples as a potential diagnostic tool for determination of phenylketonuria using MEKC with dual C 4 D/amperometric detection .…”
Section: Applications Of Electrophoresis Methods With Conventional Camentioning
confidence: 99%
“…The method was in good agreement with currently used LC/MC method (Vernez and Krahenbuhl, 2004). Vidal et al (2011a) have proposed a sensitive and fast procedure based on CE with C 4 D for the determination of fluoroacetate and fluoride in blood serum. The analysis was performed in BGE containing 15 mmol/L histidine and 30 mmol/L gluconic acid (pH 3.85).…”
Section: Biological Analysismentioning
confidence: 99%
“…Many publications report the utility of C 4 D for a wide variety of small inorganic ions [22,23] or organic ions [24,25]. This detection system is very sensitive and allows detection of inorganic and organic ions in various samples.…”
Section: Introductionmentioning
confidence: 99%